2008
DOI: 10.1186/1475-2867-8-6
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization and intensity of staining of nm23 protein is useful marker for breast cancer progression

Abstract: Background: Breast cancer is the most common cause of cancer death in the western world. The expression differences of many proteins are associated with breast cancer progression or suppression. The purpose of the study was to determine the expression of nm23 protein in the invasion status and metastatic potential of breast cancer by using tissue microarray and to determine its role in breast cancer based on the expression of nm23 gene product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…We observed that LY2109761 reduced MMP-9 in liver metastases in treated mice, whereas the MMP-2 level remained unchanged (Figure 4A). The level of nm23 is increased in highly metastatic malignancies 16, 17, 18. We observed that LY2109761 significantly reduces nm23 expression in liver metastases of treated mice when compared with control mice (Figure 4A).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…We observed that LY2109761 reduced MMP-9 in liver metastases in treated mice, whereas the MMP-2 level remained unchanged (Figure 4A). The level of nm23 is increased in highly metastatic malignancies 16, 17, 18. We observed that LY2109761 significantly reduces nm23 expression in liver metastases of treated mice when compared with control mice (Figure 4A).…”
Section: Resultsmentioning
confidence: 78%
“…Apart from this, LY2109761 also down-regulated pro-oncogenic/pro-metastatic proteins like MMP-9, uPA, and COX-2; all of which are known to be induced by TGF-β and in turn promote colorectal cancer progression. Although, reduced level of nm23 expression has been shown to be associated with aggressive tumor behavior21, high levels of nm23 expression were also noted in the advanced stages of colon, breast and thyroid carcinomas 16, 17, 18. In addition, in a related study nm23 has been shown to be upregulated in liver metastatsis in a splenic injection model 15.…”
Section: Discussionmentioning
confidence: 96%
“…9 Nuclear NME1 was observed at a higher frequency in invasive ductal carcinoma and invasive lobular carcinoma node-positive patients compared with node-negative patients, suggesting that nuclear NME1 may be a useful prognostic marker for poor outcome in breast cancer. 8 The contribution of nuclear NME1 to the poor prognosis of breast and prostate cancer 8,9 patients is currently unclear. In contrast, nuclear NME1 correlates with a favorable prognosis in laryngeal carcinoma patients.…”
Section: Nuclear Nme1 As a Potential Prognostic Marker In Cancermentioning
confidence: 99%
“…However, Epstein-Barr virus nuclear antigen 3C (EBNA-3C) promotes Nm23-H1 nuclear localization and modulate Nm23-H1 activities [46]. Ismail et al [47] showed that nuclear localization of NM23-H1 protein in breast cancer is seen more frequently in node-positive metastatic cases. They concluded that abnormal nuclear accumulation of the protein may indicate tumor progression [47].…”
Section: Discussionmentioning
confidence: 99%
“…Ismail et al [47] showed that nuclear localization of NM23-H1 protein in breast cancer is seen more frequently in node-positive metastatic cases. They concluded that abnormal nuclear accumulation of the protein may indicate tumor progression [47]. Similarly, we demonstrated that nuclear NM23-H1 was significantly positively correlated with stage.…”
Section: Discussionmentioning
confidence: 99%